UMA RELEITURA SÓCIO-HISTÓRICA NA CLÍNICA FONOAUDIOLÓGICA: INTERPRETANDO AS LACUNAS DO DISCURSO AFÁSICO - Mendes, Paulo Eduardo (Intercâmbio, 2010)
In this work, based on a Vygotskian framework, we analysed an aphasic case. It is our purpose to understand some aspects of the language process (re)organization. We realized that the gaps of the aphasic discourse, provide us with a possibility to comprehend both the relations which are kept in this new linguistic conduct, and the process involved in the therapeutic development.